ANALYSIS OF SINO-RUSSIAN AGRICULTURAL COOPERATION UNDER THE FRAMEWORK OF HEILONGJIANG FREE TRADE ZONE - Cheng, Yining; Wang, Xizhe; Nizkoshapkina, Olga (Revista Inclusiones, 2020)
Agricultural cooperation and agricultural products trade are new driving forces for the deepening economic and trade cooperation between China and Russia in recent years. Driven by the interests and needs of both China and Russia, China’s construction of a Free Trade Zone which facing Russia has achieved phased results, and agricultural cooperation has attracted much attention under the framework of the Heilongjiang Free Trade Zone. The purpose of this article is through the current situation of Sino-Russian agricultural cooperation to analyze and explain the prospects of agricultural cooperation under the framework of Chinese (Heilongjiang) FTZ. Through the analysis, the author concludes that the development focus of Heihe and Suifenhe areas in Heilongjiang FTZ is agricultural cooperation between China and Russia. The innovation of this paper is to combine the traditional research perspective of Sino Russian agricultural cooperation with the cooperation under the framework of free trade zone.